2019
DOI: 10.3346/jkms.2019.34.e170
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multidisciplinary Approach on the Birth Rate of Fetuses with Prenatally Diagnosed Congenital Heart Disease

Abstract: Background This study aimed to determine the effect of a multidisciplinary approach on the birth rate of fetuses with prenatally diagnosed congenital heart diseases (CHDs). Methods Among the fetuses of 724 gravidas who underwent fetal echocardiography in Samsung Medical Center from January 2013 to June 2017, 463 fetuses with normal cardiac structure, arrhythmia or simple left-to-right shunt were excluded, and the remaining 261 were included in the study. The subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Multidisciplinary team counseling can help family members understand precisely and comprehensively the subtype, available management and treatment options, and the long-term prognosis of fetal heart abnormalities and facilitate decision-making [37][38][39]. In keeping with recent researches [21,40], our results con rmed the signi cant impact of a multidisciplinary team approach on the pregnancy outcomes of fetal cardiac defects. In comparing the pregnancy outcomes of patients with multidisciplinary team consultation and those without, we found that the MDT group has less termination rate, which suggests that the multidisciplinary team consultation is an effective strategy to provide authoritative prognosis counseling and perinatal management of fetal cardiac defects.…”
Section: Discussionsupporting
confidence: 76%
“…Multidisciplinary team counseling can help family members understand precisely and comprehensively the subtype, available management and treatment options, and the long-term prognosis of fetal heart abnormalities and facilitate decision-making [37][38][39]. In keeping with recent researches [21,40], our results con rmed the signi cant impact of a multidisciplinary team approach on the pregnancy outcomes of fetal cardiac defects. In comparing the pregnancy outcomes of patients with multidisciplinary team consultation and those without, we found that the MDT group has less termination rate, which suggests that the multidisciplinary team consultation is an effective strategy to provide authoritative prognosis counseling and perinatal management of fetal cardiac defects.…”
Section: Discussionsupporting
confidence: 76%
“…The fact that multi-disciplinary counselling that includes cardiac surgeons can influence the termination rate of pregnancies, particularly in the case of univentricular heart defects, has recently been described. 27…”
Section: Discussionmentioning
confidence: 99%
“…This fall in birth rate is a serious problem for Korea because the stabilization of fertility at such a low level inevitably results in accelerated population aging and depopulation (Seo, 2019). Despite the government's efforts to encourage childbirth, the low birth rate issue has not improved in Korea because of the aspirations of its working‐class women and residence pattern changes (Kim et al, 2019).…”
Section: The Challenges For Koreamentioning
confidence: 99%